Patient Registry of Spasticity Care World: Data Analysis Based on Physician Experience. (December 2017) - Esquenazi, Alberto; Lee, Stella; Mayer, Nathaniel; Garreta, Roser; Patel, Atul; Elovic, Elie; Koelbel, Stephen; Francisco, Gerard; Reuter, Iris
Abstract : Objective: The aim of the study was to report physician experience–based "real-world" treatment patterns with botulinum toxin type A in patients with stroke and traumatic brain injury. Design: A prospective, multicenter, international observational registry design was used. Results: Six hundred twenty-seven participants with stroke and 132 participants with traumatic brain injury were assessed and treated by 17 more experienced physicians and 12 less experienced physicians. Due to the limited usage of abobotulinumtoxinA Dysport and incobotulinumtoxinA Xeomin, data were reported on onabotulinumtoxinA BOTOX only. Based on physician experience, onabotulinumtoxinA doses were statistically different with larger mean doses injected by more experienced physicians in the upper limb (59.9 [39.0], P = 0.001) and in the lower limb (101.8 [69.2], P < 0.001). Treated deformities significantly differed for both upper limb and lower limb ( P < 0.001). More experienced physicians showed a larger mean change in Ashworth Scale scores from baseline for the equinovarus/equinus foot and stiff knee ( P = 0.001 and 0.03). Less experienced physicians showed a larger mean change in Ashworth Scale scores from baseline for the adducted thigh ( P = 0.05). Less experienced physicians had statistically significant larger change in hand pain scores for clenched fist deformity treatment at follow-up compared with more experienced physicians ( P = 0.01). Physician experience demonstrated a significant difference on patients reported satisfaction toward their secondary goal with higher scores for more experienced physician ( P = 0.04). Conclusions: This international registry provides clinical nuances of treatment based on physician clinical experience in a robust sample size. Abstract : Supplemental digital content is available in the text.